Ultrastructural characterization and three-dimensional architecture of replication sites in dengue virus-infected mosquito cells - Jiraphan Junjhon (2018)
During dengue virus infection of host cells, intracellular membranes are rearranged into distinct subcellular structures such as double-membrane vesicles, convoluted membranes, and tubular structures. Recent electron tomographic studies have provided a detailed three-dimensional architecture of the double-membrane vesicles, representing the sites of dengue virus replication, but temporal and spatial evidence linking membrane morphogenesis with viral RNA synthesis is lacking. Integrating techniques in electron tomography and molecular virology, we defined an early period in virus-infected mosquito cells during which the formation of a virus-modified membrane structure, the double-membrane vesicle, is proportional to the rate of viral RNA synthesis. Convoluted membranes were absent in dengue virus-infected C6/36 cells. Electron tomographic reconstructions elucidated a high-resolution view of the replication complexes inside vesicles and allowed us to identify distinct pathways of particle formation. Hence, our findings extend the structural details of dengue virus replication within mosquito cells and highlight their differences from mammalian cells. © 2014, American Society for Microbiology.